Antibacterial properties of honey and green tea extracts against multi-drug resistant streptococcus mutans isolated from dental plaque samples - CHOWDAIAH. M,; DHAMODHAR. P, (International Journal of Pharma and Bio Sciences, 2017)
Streptococcus mutans is the major etiological agent for the dental plaque formation. A study on the occurrence of multidrug resistant (MDR) Streptococcus mutans and control of S. mutans isolated from dental caries patients against green tea and honey extracts among the Bangalore urban population as in search of alternate therapy for dental caries. In this study, 118 dental plaque samples were collected and 87 were identified as MDR S. mutans isolates by using biochemical tests, Disc-diffusion test against commercial antibiotics and antibacterial property of green tea & honey against 10 MDR S. mutans isolates was done by using agar well diffusion method. The zone diameters (mm) of each isolate against selected antibiotics obtained were noted and compared with reference antibiotics namely ciprofloxacin, erythromycin and penicillin G. The zone diameters of Green tea organic and aqueous extracts were ranged from 14mm to 29mm. Similarly, for Honey extracts it ranged from 4-18mm. The antibiograms of green tea extracts has revealed that the MDR S. mutans is sensitive to these at 100mg/ml concentration. The antibiograms of honey with different dilutions has revealed that, with dilution the activity got reduced and found sensitive with no dilution. The MIC of green tea and honey used were found to be 70mg/ml and 100mg/ml respectively with 50µl loaded to the wells. The study revealed that the Green tea and Honey were equally effective to ciprofloxacin and erythromycin in controlling MDR S. mutans.